A negative electrode for power battery and preparation method thereof

The negative electrode of lithium-ion battery is prepared through cold spraying technology, and the network structure is formed using copper, silicon and rigid polymers, which solves the problems of poor uniformity and insufficient conductivity of the negative electrode of existing lithium-ion battery, and achieves the high performance and long life of the negative electrode of the battery. .

CN116504916BActive Publication Date: 2025-02-25HUBEI CHAOZHUO AVIATION TECHNOLOGY GROUP CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310413355.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-18
Publication Date
2025-02-25
Estimated Expiration
2043-04-18

AI Technical Summary

Technical Problem

The existing lithium-ion battery anode materials have problems such as poor uniformity, insufficient conductivity, high impedance, low bonding strength and fast battery capacity decay, which is difficult to meet the needs of new energy vehicles for high energy density, high power and fast charging and discharge.

Method used

The negative electrode of the battery is prepared by cold spraying technology, and the network structure is formed using copper, silicon and rigid polymers to improve the uniformity, conductivity and bonding strength of the negative electrode active material layer, reduce impedance and delay the attenuation of battery capacity.

Benefits of technology

It achieves the characteristics of excellent uniformity, good conductivity, low impedance, high bonding strength and slow battery capacity attenuation, ensuring the service life and charge and discharge efficiency of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116504916B_ABST
    Figure CN116504916B_ABST
Patent Text Reader

Abstract

The present invention discloses a negative electrode for a power battery and a preparation method thereof, which belongs to the technical field of new energy batteries. The key points of the technical scheme are: the negative electrode includes a current collector and a negative electrode active material layer, the negative electrode active material layer is fixedly connected to the surface of the current collector by a cold spraying process, and the negative electrode active material layer includes copper, silicon and a rigid polymer; the preparation steps of the negative electrode are: S1, crushing the rigid polymer into ultrafine powder; S2, mixing the ultrafine powder, copper powder and silicon powder uniformly according to the weight ratio to obtain a mixed powder; S3, spraying the mixed powder onto the surface of the current collector by a cold spraying process. The present invention prepares the negative electrode of the battery by cold spraying, the process is simple, the process is stable, the prepared product has good consistency, and can effectively guarantee the battery life; the product has the characteristics of good uniformity, good conductivity, low impedance, high bonding strength and slow battery capacity decay.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy batteries, and in particular to a negative electrode for a power battery and a preparation method thereof. Background Art

[0002] The development of new energy vehicles is gradually tending towards achieving high energy density, high power and fast charging and discharging. This development trend also puts higher requirements on the power batteries of new energy vehicles.

[0003] The power battery of new energy vehicles is assembled from battery boxes, battery management systems, battery modules and auxiliary components. Among them, the battery box is used to provide waterproof, dustproof, anti-vibration and other protections for the battery system, and also provides a mechanical interface for the installation of the battery system; the battery management system is used to manage the charge and discharge of the battery and the communication; auxiliary components include relays, fuses, heating systems, etc., and their main function is to control and protect the circuit; the battery module is a combination of several to hundreds of single cells connected in parallel or in series.

[0004] A single cell includes a positive electrode sheet, a negative electrode sheet, a separator, an electrode tab, an electrolyte, a packaging film, etc. Among them, the positive electrode sheet is generally composed of an aluminum foil and a positive electrode material coated on the aluminum foil, and the negative electrode sheet is generally composed of a copper foil and a negative electrode active material layer coated on the copper foil.

[0005] Taking lithium batteries as an example, the positive electrode material is generally made of high-purity lithium-containing metal oxides, and the negative electrode active material layer is generally made of graphite. However, with the development of new energy vehicles, graphite materials, as the most commonly used negative electrode active material layer of lithium-ion batteries, have the following disadvantages:

[0006] 1) The production process of battery pole pieces is relatively long, including ball milling, mixing, coating, rolling, cutting, winding and other processes. Therefore, the performance of battery pole pieces will be greatly affected by factors such as material uniformity, slurry dispersion uniformity, coating uniformity, rolling, welding, etc., which will cause different single cells to have differences in voltage, capacity, impedance and other performance, and then make the charging and discharging end points of single cells used in series and parallel inconsistent, which ultimately makes it difficult to guarantee the consistency and life of the battery.

[0007] 2) With the increase of positive electrode capacity, corresponding requirements are also put forward for the capacity of negative electrode. Currently, the most widely used technology route is silicon-based negative electrode. However, silicon-based negative electrode currently has the disadvantages of easy collapse and pulverization of material structure, which leads to poor cycle performance of battery and rapid decay of battery capacity.

[0008] In order to solve the above problems, a negative electrode for a power battery and a preparation method thereof are provided on the basis of the prior art. Summary of the invention

[0009] The object of the present invention is to provide a negative electrode for a power battery and a preparation method thereof. The present invention adopts a cold spraying process to prepare the battery negative electrode, which has the characteristics of good uniformity, good conductivity, low impedance, high bonding strength, and slow battery capacity decay; and the cold spraying process for preparing the battery negative electrode is simple, the process is stable, and the prepared product has good consistency, which can effectively guarantee the battery life; and, by forming a network structure through rigid polymers and silicon-based materials, the structural framework can be effectively maintained to ensure that there is always enough lithium ion embedding space in the negative electrode active material layer, thereby effectively reducing the battery capacity decay rate.

[0010] The above technical objectives of the present invention are achieved through the following technical solutions:

[0011] The present invention provides a negative electrode for a power battery. The negative electrode comprises a current collector and a negative electrode active material layer. The negative electrode active material layer is fixedly connected to the surface of the current collector by a cold spraying process.

[0012] By adopting the above technical solution and utilizing the cold spraying process, it is helpful to make the negative electrode active material layer sprayed on the current collector have better uniformity, conductivity, and thermal conductivity, which can effectively reduce the impedance; and the cold spraying process can make the bonding strength between the current collector and the negative electrode active material layer higher, thereby effectively avoiding the growth of the passivation film caused by cracks in the negative electrode active material layer, and further effectively avoiding the rapid attenuation of the battery capacity.

[0013] In addition, the cold spraying process can better ensure the consistency between lithium-ion single cells. In the existing technology, the battery production process is long, and various processes in the production process will cause errors in different batches or even the same batch of single cells, thereby causing differences in the voltage, capacity, impedance and other performance of the single cells. The cold spraying technology has the characteristics of stable process and simple process, and can ensure to a large extent that the charging and discharging end points of single cells used in series and parallel are consistent, so as to ensure the service life of the battery.

[0014] The present invention is further configured as follows: the negative electrode active material layer includes copper, silicon and a rigid polymer.

[0015] By adopting the above technical solution, silicon is one of the most abundant elements on earth, and it can form Li 12 Si 7 , Li 13 Si 4 , Li 7 Si 3 , Li 22 Si 5 , Li 15 Si 4And other alloys, so it has a very high capacity, can be matched with a high-capacity positive electrode to meet the high-capacity needs of power batteries; the lithium insertion voltage of silicon is lower than 0.5V, but slightly higher than graphite, which means that during charging, there is basically no lithium deposition on the surface, so it has better safety.

[0016] During the battery charging and discharging process, the negative electrode coating material will repeatedly undergo the process of lithium insertion and removal. The general silicon-based material will expand in volume during the lithium insertion process, which will produce huge internal stress, causing cracks and powderization in the negative electrode active material layer, thereby causing the electrolyte to further contact and react with the inside of the coating, and then causing the passivation film on the electrode surface to thicken; the process of passivation film thickening will consume more lithium ions, thereby reducing the battery capacity; after lithium removal, the silicon-based material will collapse in structure, and the lithium insertion space will be greatly reduced, which will further reduce the battery capacity; and the thickening of the passivation film will also have a negative impact on the migration process of lithium ions, thereby affecting the charging and discharging efficiency; in addition, silicon itself has low electrical conductivity.

[0017] The network structure is formed by using a rigid polymer and a silicon-based material. Firstly, since the structure itself has a large amount of embedding space, it can effectively prevent lithium precipitation, thereby effectively avoiding perforation of the diaphragm due to lithium precipitation, and has higher safety. Secondly, the component can provide a rigid structural support for the silicon-based negative electrode active material layer, which helps to effectively solve the problem of reduced embedding space caused by structural collapse of silicon-based materials during repeated lithium embedding and de-embedding, and ensure that there is always enough lithium ion embedding space in the negative electrode active material layer. Thirdly, the component can limit the volume expansion of the silicon-based negative electrode after lithium embedding, thereby further playing a role in maintaining the structural framework, and can effectively avoid cracking and powdering of the coating caused by excessive internal stress, thereby effectively preventing the thickening of the passivation film, reducing the loss of lithium ions, and further reducing the rate of capacity decay. In addition, the rigid polymer has the characteristics of high temperature resistance, and can keep the frame structure intact without breaking or powdering at the operating temperature of the electrode.

[0018] The negative electrode active material layer including copper, rigid polymer and silicon is bonded to the current collector through a cold spraying process. The uniform mixing of copper, rigid polymer and silicon helps to enhance the bonding strength inside the negative electrode active material layer and between the negative electrode active material layer and the current collector, thereby effectively maintaining the battery capacity and improving the charge and discharge efficiency. In addition, copper has excellent conductivity, which can effectively improve the conductivity of the negative electrode active material layer.

[0019] The present invention is further configured as follows: the rigid polymer contains a plurality of ester groups and a plurality of benzene rings.

[0020] By adopting the above technical solution, it is helpful to make oxygen and silicon in the rigid polymer form O-Si-O covalent bonds, which can provide rigid structural support for the silicon-based negative electrode active material layer on the one hand, and on the other hand, it can limit the volume expansion of the silicon-based negative electrode after lithium insertion, play a role in maintaining the structural framework, and ensure that there is always enough space for lithium ion embedding in the negative electrode active material layer, which can effectively reduce the attenuation rate of the battery capacity.

[0021] The present invention is further configured as follows: the rigid polymer is polybenzoxazine.

[0022] By adopting the above technical solution, polybenzoxazine has high thermal stability, thermal oxidation resistance, chemical resistance and high mechanical strength, and can form a framework structure with a certain strength with silicon-based materials. In the process of repeated lithium insertion and extraction, it is ensured that there is always enough lithium ion insertion space in the negative electrode active material layer, which can effectively reduce the attenuation rate of battery capacity; on the other hand, the component also has a certain viscosity, which can further improve the cohesion of the coating, thereby effectively maintaining the battery capacity and improving the charging and discharging efficiency.

[0023] The present invention is further configured such that: the negative electrode active material layer also includes superconducting carbon black.

[0024] The adoption of the above technical solution helps to further improve the conductivity of the negative electrode coating and compensate for the electronic conductivity of the negative electrode active material layer.

[0025] The present invention is further configured as follows: the weight ratio of the copper, silicon, rigid polymer and conductive agent is 5-9%: 87-93%: 2-3%: 0-1%.

[0026] By adopting the above technical solution, it is helpful to form a negative electrode active material layer with good conductivity, large capacity, good battery cycle performance and slow battery capacity decay.

[0027] The present invention also provides a method for preparing a negative electrode for a power battery, which is characterized by comprising the following steps:

[0028] S1, crushing the rigid polymer into ultrafine powder;

[0029] S2, mixing the ultrafine powder, copper powder and silicon powder uniformly according to a weight ratio to obtain a mixed powder;

[0030] S3, spraying the mixed powder onto the surface of the current collector by cold spraying process.

[0031] By adopting the above technical solution, it is helpful to obtain a battery negative electrode with uniformity, better electrical and thermal conductivity, low impedance, high bonding strength, good cycle performance, slow battery capacity decay, and consistency.

[0032] The present invention is further configured as follows: the crushing equipment described in step S1 is a jet mill or a cryogenic mill; and the uniform mixing device described in step S2 is a super ball mill.

[0033] The present invention is further configured as follows: the particle size of the ultrafine powder is 5-50 μm.

[0034] By adopting the above technical solution, powder suitable for cold spraying can be obtained.

[0035] The present invention is further configured as follows: the cold spraying working gas described in step S3 is one or more of air, nitrogen or helium; the spraying pressure of the cold spraying is 1 to 8 MPa; the spraying temperature of the cold spraying is 150 to 1000°C; the gas velocity of the cold spraying is 150 to 1100 m / s; and the spraying distance of the cold spraying is 5 to 120 mm.

[0036] By adopting the above technical solution, a battery negative electrode with excellent performance can be obtained.

[0037] In summary, the present invention has the following beneficial effects:

[0038] 1. The present invention adopts a cold spraying process to prepare the battery negative electrode, which has the characteristics of good uniformity, good conductivity, low impedance, high bonding strength, and slow battery capacity decay; and the cold spraying process for preparing the battery negative electrode is simple, the process is stable, and the prepared product has good consistency, which can effectively guarantee the battery life;

[0039] 2. The present invention forms a network structure through rigid polymers and silicon-based materials. On the one hand, it can provide rigid structural support for the silicon-based negative electrode active material layer, and on the other hand, it can limit the volume expansion of the silicon-based negative electrode after lithium insertion, play a role in maintaining the structural framework, and ensure that there is always enough lithium ion embedding space in the negative electrode active material layer, which can effectively reduce the attenuation rate of the battery capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 It is a schematic diagram of the structural position of the negative electrode of the battery;

[0041] In the figure: 1. positive electrode; 2. negative electrode; 3. separator. DETAILED DESCRIPTION

[0042] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments:

[0043] like Figure 1 As shown, the structure of a single cell is composed of a shell, a positive electrode, a negative electrode, a separator, etc. This technical solution mainly improves the performance of the negative electrode.

[0044] Embodiment 1: A negative electrode for a power battery, the negative electrode comprising a current collector and a negative electrode active material layer, the negative electrode active material layer is fixed to the surface of the current collector by a cold spraying process, and the current collector is a copper foil; the negative electrode active material layer comprises copper, silicon and a rigid polymer; the rigid polymer contains multiple ester groups and multiple benzene rings; the rigid polymer is polybenzoxazine; the weight ratio of copper, silicon and rigid polymer is 5%:93%:2%.

[0045] The preparation method of the polybenzoxazine comprises the following steps: using phenolphthalein, aniline and formaldehyde as raw materials to prepare a benzoxazine intermediate, and obtaining a high-performance polybenzoxazine resin containing a phenolphthalein structure through thermal curing.

[0046] Example 2: The difference from Example 1 is that the negative electrode active material layer also includes superconducting carbon black; the weight ratio of copper, silicon, rigid polymer and conductive agent is 6%:90%:3%:1%.

[0047] Example 3: The difference from Example 2 is that the weight ratio of copper, silicon, rigid polymer and conductive agent is 7%:90%:2.5%:0.5%.

[0048] Example 4: The difference from Example 2 is that the weight ratio of copper, silicon, rigid polymer and conductive agent is 8%:88%:3%:1%.

[0049] Example 5: The difference from Example 2 is that the weight ratio of copper, silicon, rigid polymer and conductive agent is 9%:87%:3%:1%.

[0050] Example 6: A method for preparing a negative electrode for a power battery, the steps are as follows:

[0051] S1. Grind the rigid polymer into ultrafine powder, the particle size of the ultrafine powder is 5-50 μm, and the grinding equipment is a jet mill or a cryogenic mill;

[0052] S2, mixing the ultrafine powder, copper powder, silicon powder and conductive agent in a weight ratio of 6%:90%:3%:1% to obtain a mixed powder, and the mixing device is a super ball mill;

[0053] S3. Spray the mixed powder onto the surface of the copper foil current collector through a cold spraying process; the cold spraying working gas is one or more of air, nitrogen or helium; the spraying pressure of the cold spraying is 1Mpa; the spraying temperature of the cold spraying is 1000°C; the gas velocity of the cold spraying is 1100m / s; and the spraying distance of the cold spraying is 120mm.

[0054] Example 7: The difference from Example 6 is that: the spraying pressure of cold spraying is 8 MPa; the spraying temperature of cold spraying is 150°C; the gas velocity of cold spraying is 150 m / s; and the spraying distance of cold spraying is 5 mm.

[0055] Example 8: The difference from Example 6 is that: the spraying pressure of cold spraying is 4 MPa; the spraying temperature of cold spraying is 500°C; the gas velocity of cold spraying is 460 m / s; and the spraying distance of cold spraying is 30 mm.

[0056] Example 9: The difference from Example 6 is that: the spraying pressure of cold spraying is 6 MPa; the spraying temperature of cold spraying is 800°C; the gas velocity of cold spraying is 820 m / s; and the spraying distance of cold spraying is 80 mm.

[0057] Comparative Example 1: The difference from Example 2 is that the artificial graphite blocks are crushed, graded and shaped to obtain artificial graphite powder, asphalt and artificial graphite powder are mixed in a weight ratio of 1:30, treated at 800°C for 2 hours under the protection of an inert gas, and then cooled to room temperature and then broken up, sieved and demagnetized to obtain a sample, and the sample, styrene-butadiene rubber latex and carbon black are mixed in a weight ratio of 96:3:1 to form powder, which is coated on a copper foil electrode by a cold spraying process.

[0058] Comparative Example 2: The difference from Example 6 is that the ultrafine powder, copper powder, silicon powder and conductive agent are mixed in a weight ratio of 6%:90%:3%:1% to form a slurry, which is coated on a copper foil and dried to form a negative electrode.

[0059] Detection: The above-prepared product is used as the negative electrode of lithium-ion battery; lithium is used as the counter electrode and 1M LiPF is used as the electrolyte 6 A mixture of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) was prepared, wherein the mass ratio of the three components was 1:1:1, and the separator was a PE / PP / PE composite film. The simulated battery was assembled at 0.5 mA / cm 2 The constant current charge and discharge experiment was carried out at a current density of (0.2C), and the charging voltage was limited to 0.01-2.0V. The first charge specific capacity, first discharge specific capacity and 1000 cycle performance (%) of the negative electrode active material layer were tested. The electrochemical performance test results are as follows:

[0060] Example First discharge specific capacity mAh / g First charge specific capacity mAh / g 1000 cycle performance (%) Example 1 1003 953 82.3 Example 2 1013 962 82.6 Example 6 1011 964 82.1 Example 9 1017 972 82.7 Comparative Example 1 411 399 82.7 Comparative Example 2 865 796 62.8

[0061] From the above, it can be seen that the present invention adopts the cold spraying process to prepare the battery negative electrode, which has the characteristics of good uniformity, good conductivity, low impedance, high bonding strength, and slow battery capacity decay; and the process of cold spraying to prepare the battery negative electrode is simple, the process is stable, and the prepared product has good consistency, which can effectively ensure the battery life.

[0062] In addition, by forming a network structure through rigid polymers and silicon-based materials, the structural framework can be effectively maintained, ensuring that there is always enough space for lithium ions to be embedded in the negative electrode active material layer, thereby effectively reducing the attenuation rate of the battery capacity.

[0063] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.

Claims

1. A negative electrode for a power battery, characterized in that: The negative electrode comprises a current collector and a negative electrode active material layer, wherein the negative electrode active material layer is fixedly bonded to the surface of the current collector by a cold spraying process; the negative electrode active material layer comprises copper, silicon and a rigid polymer; the rigid polymer contains a plurality of ester groups and a plurality of benzene rings; the rigid polymer is polybenzoxazine; The steps for preparing the negative electrode for power batteries are as follows: S1, crushing the rigid polymer into ultrafine powder, wherein the particle size of the ultrafine powder is 5-50 μm; S2, mixing the ultrafine powder, copper powder and silicon powder uniformly according to a weight ratio to obtain a mixed powder; S3. Spray the mixed powder onto the surface of the current collector through a cold spraying process, the cold spraying working gas is one or more of air, nitrogen or helium; the spraying pressure of the cold spraying is 4 to 8 MPa; the spraying temperature of the cold spraying is 150 to 1000°C; the gas velocity of the cold spraying is 150 to 1100 m / s; the spraying distance of the cold spraying is 5 to 120 mm.

2. A negative electrode for a power battery according to claim 1, characterized in that: The negative electrode active material layer further includes superconducting carbon black.

3. The negative electrode for a power battery according to claim 1, characterized in that: The crushing equipment in step S1 is a jet mill or a cryogenic mill; the mixing device in step S2 is a super ball mill.

Citation Information

Patent Citations

  • Electrode, power storage device, electronic device, and manufacturing method of electrode

    US20160190592A1